2020
DOI: 10.1177/1557988320982702
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between African American Father–Child Relationships and HIV Testing

Abstract: The existing literature identifies parent communication as a protective mechanism in the reduction of sexual risk behaviors among youth; however, not much is known about father–child communication and bonding and its association with HIV testing. Therefore, this study examines the link between the relationship, bonding, and communication shared by African American (AA) fathers and their children and HIV testing over time. This secondary data analysis included data from Waves 1 and 3 of the National Longitudina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 21 publications
3
14
0
Order By: Relevance
“…Our findings indicated that an increase in parent–child sexual communication, parental bonding, and lower levels of peer pressure decreased the prevalence rate of drug use among Black youth. These findings are consistent with the prior literature that parental factors can be protective for Black youth [ 21 , 24 ]. Our results also indicated that youth who did not experience peer pressure were less likely to have sex while under the influence of alcohol or drugs, which suggests the effect of the mesosystem on Black youth and young adults in this sample.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings indicated that an increase in parent–child sexual communication, parental bonding, and lower levels of peer pressure decreased the prevalence rate of drug use among Black youth. These findings are consistent with the prior literature that parental factors can be protective for Black youth [ 21 , 24 ]. Our results also indicated that youth who did not experience peer pressure were less likely to have sex while under the influence of alcohol or drugs, which suggests the effect of the mesosystem on Black youth and young adults in this sample.…”
Section: Discussionsupporting
confidence: 93%
“…Parent–child communication has been shown to be a significant protective factor for youth [ 21 , 24 ], and evidence has indicated that parent–child communication is the preferred source of quality sexual health education as well as an effective means of maintaining sexual well-being among urban Black youth [ 25 , 26 ]. Black male youth residing in the inner city whose mothers are supportive and openly communicate with them about their sexual health are less likely to take sexual risks that lead to unprotected sex, unwanted pregnancies, and HIV and other STIs [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parental bonding is a subjective experience of affection from a parent towards a child. The core tenet of the bond is the perceived feeling of "love" expressed in parental behavior [15][16][17]. There is a dearth of literature on parental bonding in BLMSM and its effects on their PrEP attitudes, stigma, and use and perceptions of stigma.…”
Section: Introductionmentioning
confidence: 99%
“…Parent Relationships was measured using a 7-item scale, and the items have been used in prior research [ 37 , 38 , 39 ]. Study respondents were asked questions such as “how disappointed would your parents be if you did not graduate from high school” and “how well do your parents know how you spend money?” The response categories ranged from 1 = not at all to 5 = very much, and higher scores indicated an increase in parent–child relationships.…”
Section: Methodsmentioning
confidence: 99%